Un modelo de educación de calidad en economía y dirección de empresas - Rivera Camino, Jaime (2011)
The literature acknowledges the importance of the education in Economics and Business Administration for the competitiveness of all countries. However, what exactly is educational quality in this discipline has been insufficiently studied. The objective of this paper is to contribute in this area by putting forward a conceptual model to assess and monitor quality in higher education. Our study intends to provide information that is significant to the lecturers and higher education managers that compete in an international knowledge-based economy, and particularly in Europe, and more precisely in Spain, in the European Higher Education Area.